Empowering Community Health Cadres in Monitoring Toddler Growth and Development Through The Maternal and Child Health (MCH) Book Counseling for Stunting Screening - Dyah Noviawati Setya Arum; Masrif Masrif; Sumarah Sumarah; Linda Nur Wahyuni (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Cadres are the drivers of various aspects of society's social life. Health cadres are one of the partners of health workers who are expected to be able to bridge between health workers and the community, helping improve the health and welfare of people in the region. The principle of community empowerment is applied in health development programs; one example is the Integrated Service Post (Posyandu). Posyandu is an activity that is managed and organized from, by, for, and with the community. The aim of community service activities is to provide education about the KIA book to health cadres. The target of the activity was health cadres, totaling 20 participants. The methods used were lectures, questions, and answers using the KIA book as tools and presentation material about the use of the KIA book. Evaluation of community service activities by assessing pre-test and post-test regarding knowledge of KIA book use by cadres. The post-test was carried out after participants received information about using the KIA book. The results of the activity showed an average pre-test score of 60.71 and an average post-test score of 72.85. The conclusion of this community service activity was that there was an increase in the level of knowledge of health cadres in using KIA books to monitor the growth and development of toddlers as an effort to screen for early stunting.